Understanding of the color in composite resin - Jeong-Won Park (Korean Academy of Conservative Dentistry, 2011)
In clinic, esthetic restoration of a defective natural tooth with composite resin is challenging procedure and needs complete understanding of the color of tooth itself and materials used. The optical characteristics of the composites are different because the chemical compositions and microstructures are not same. This review provided basic knowledge of the color and the color measurement devices, and analyze the color of the natural tooth. Further, the accuracy of the shade tab, color of the composite resins before and after curing, effect of the water, food and bleaching agent, and translucency, opalescence, and fluorescence effects were evaluated.